2021
DOI: 10.1371/journal.pone.0259211
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase in the development of nephrogenic systemic fibrosis (NSF)-like skin lesion in renal failure mouse model

Abstract: Although neutrophil elastase (NE) may play a role in lung fibrosis and liver fibrosis, NE involvement in the development of nephrogenic systemic fibrosis has been unclear. We investigated the involvement of NE in the development of nephrogenic systemic fibrosis-like skin lesions post-injections of linear gadolinium-based contrast agents in renal failure mouse models. Renal failure mouse models were randomly divided into three groups: control group (saline), gadodiamide group, and gadopentetate group. Each solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…ELANE and CTSG are neutrophil serine proteases (NSPs); they are stored in the cytoplasmic granules of neutrophils and secreted into the extracellular space upon activation and are closely related to regulation of bacterial defense processes and inflammatory responses in local tissues, playing an important role in the process of chronic inflammatory injury. 21 Previous studies have shown that ELANE and CTSG play an important immunomodulatory role in many immune diseases, mainly related to neutrophil activation 22 ; ELANE is also closely associated with immunological and pathological damage in pulmonary cystic fibrosis. 23 In addition, ELANE is closely associated with the fibrotic process in various tissues and organs, such as lung fibrosis and liver fibrosis 24 ; thus, we experimentally validated the role of these two key differential proteins in the pathological process of PANDO.…”
Section: Discussionmentioning
confidence: 99%
“…ELANE and CTSG are neutrophil serine proteases (NSPs); they are stored in the cytoplasmic granules of neutrophils and secreted into the extracellular space upon activation and are closely related to regulation of bacterial defense processes and inflammatory responses in local tissues, playing an important role in the process of chronic inflammatory injury. 21 Previous studies have shown that ELANE and CTSG play an important immunomodulatory role in many immune diseases, mainly related to neutrophil activation 22 ; ELANE is also closely associated with immunological and pathological damage in pulmonary cystic fibrosis. 23 In addition, ELANE is closely associated with the fibrotic process in various tissues and organs, such as lung fibrosis and liver fibrosis 24 ; thus, we experimentally validated the role of these two key differential proteins in the pathological process of PANDO.…”
Section: Discussionmentioning
confidence: 99%
“…Other inflammatory changes have been highlighted, including the alterations in macrophage profile, though the effect on macrophage polarization, into M1 phenotype or anti-inflammatory M2 phenotype, is controversial [27,43,69]. Increase in liver M2 cells in aged animals [43], involvement of lysosomes in Gd (III) accumulation in macrophages and in their proliferation [100], leukocytic infiltration, at the renal level with tubules atrophy [50], enhancement of neutrophil elastase activity [35], and alteration in leukocyte count [37,68] were also reported. Exposure to Gd (III) prompted its phagocytosis by the mononuclear phagocytic system [110].…”
Section: Reference Study Design Main Findingsmentioning
confidence: 99%
“…Few studies using animal models of renal failure have addressed the impact of kidney disease in the toxicity of GBCAs [11,35,57,67,75,76]. Nonetheless, they suggested that, in the case of renal disease, GBCAs decreased renal function [75], triggered skin fibrosis [11,57], increased the number of fibrocytes (related to the oxidative stress environment) [76], enhanced the differentiation of mononuclear cells into ferroportin-expressing fibrocystic cells [67], produced renal tube vacuolization [11], and caused disturbances in iron metabolism and TBARS values [75], as well as increased neutrophil count and neutrophil elastase activity [35].…”
Section: Reference Study Design Main Findingsmentioning
confidence: 99%